Integrated reports, external assurance and financial performance: An empirical analysis on North American firms. Issue 2 (21st October 2019) - Akisik, Orhan; Gal, Graham
Abstract : Purpose: The purpose of this paper is to examine the relationship between integrated reports, external assurance and financial performance for North American firms between 2011 and 2016. Design/methodology/approach: Corporate websites were examined for disclosures which included both financial and non-financial information. Compustat North America and Global Reporting Initiative (GRI) websites provided additional data for the analysis. Findings: Using a panel data analysis, the results provide evidence that there is a significant positive association between integrated reports and multiple measures of financial performance. Moreover, this positive effect is enhanced when integrated reports are assured by accounting firms. Research limitations/implications: There are relatively a small number of firms that do this kind of reporting. A major limitation of the study is the small sample size. Practical implications: As stakeholders find information in integrated reports relevant, there needs to be standardization on their content and level of assurance. Standard setters and regulators should be involved in setting these standards and assurance guidelines. Social implications: Although it is clear that there is a cost to firms which produce integrated reports, the benefits to society may outweigh these costs. This may go beyond the benefits to shareholders as they make investment decisions. Originality/value: According to the knowledge of the authors, this is the first study that examines the impact of integrated reports and external assurance on financial performance for North American firms.